2004
DOI: 10.1177/0146167204264078
|View full text |Cite
|
Sign up to set email alerts
|

Playboy Playmate Curves: Changes in Facial and Body Feature Preferences Across Social and Economic Conditions

Abstract: Past research has investigated ideals of beauty and how these ideals have changed across time. In the current study, facial and body characteristics of Playboy Playmates of the Year from 1960-2000 were identified and investigated to explore their relationships with U.S. social and economic factors. Playmate of the Year age, body feature measures, and facial feature measurements were correlated with a general measure of social and economic hard times. Consistent with Environmental Security Hypothesis prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 55 publications
5
74
1
Order By: Relevance
“…More recently, a series of studies showed that men's preferences for women's weight depended on whether they felt hungry [34][35]. The direction of these effects was also consistent with the Environmental Security Hypothesis, such that men with fewer resources (less money or food) preferred heavier women [36]. However, the results described above are not very consistent and, moreover, cultural variation in social norms, ideologies, and lifestyle may cause additional variation in men's preferences for women's weight [9].…”
Section: Introductionmentioning
confidence: 73%
“…More recently, a series of studies showed that men's preferences for women's weight depended on whether they felt hungry [34][35]. The direction of these effects was also consistent with the Environmental Security Hypothesis, such that men with fewer resources (less money or food) preferred heavier women [36]. However, the results described above are not very consistent and, moreover, cultural variation in social norms, ideologies, and lifestyle may cause additional variation in men's preferences for women's weight [9].…”
Section: Introductionmentioning
confidence: 73%
“…In some studies, the faces represented were of beauty contest competitors [CUNNINGHAM 1986], models [JONES 1995, NGUYEN and TURLEY 1998, PETTIJOHN and JUNGEBERG 2004, YEHEZKEL and TURLEY 2004, and actresses [FERRARIO et al 1995, PETTIJOHN andTESSER 1999], or in works of art [COSTA and CORAZZA 2006]. The judges were sometimes orthodontists or maxillofacial surgeons (e.g., MAPLE et al [2005]), or pedophiles and rapists [MARCUS and CUNNINGHAM 2003].…”
Section: Methodsmentioning
confidence: 99%
“…However, when social and economic times are prosperous, people prefer others with more neotenous characteristics, such as larger eyes, smaller chins, rounder faces, and smaller body builds. Pettijohn and his colleagues found these patterns with regard to American movie actresses (Pettijohn & Tesser, 1999), Playboy Playmates (Pettijohn & Jungeberg, 2004) and in the laboratory where male and female participants showed a preference to work with a female partner who had smaller eyes over a partner with larger eyes in high threat conditions (Pettijohn & Tesser, 2005). The facial feature preferences for males, however, have been more variable and less systematic (Pettijohn & Tesser, 2003).…”
Section: Environmental Conditions and Musician Characteristicsmentioning
confidence: 98%